PENGAJIAN MALAM JUMAT SEBAGAI WUJUD LIVING QUR’AN DAN SUNNAH DALAM KEHIDUPAN MASYARAKAT LINK.TEGAL WANGI ASEM GEBOG, KOTA CILEGON - Fildzah Aulia Nur Muharromah; Muhammad Alif (Adisam Publisher, 2026)
This study aims to explore the function of Friday night recitation at Link. Tegal Wangi Asem Gebog as a representation of the living Qur'an and sunnah integrated into the social and religious life of the village community. The methods used include direct observation of recitation activities and semi-structured interviews with several community members, including recitation leaders, female religious teachers, and local community leaders. This study focuses on two main aspects, namely the interpretation of recitation as the active application of the teachings of the Qur'an and Sunnah, and its role in building community life and solidarity in the local community. The approach used in this study is descriptive qualitative through non-participant observation, field data collection, and simple documentation. The findings of the study show that Friday night recitation not only functions as a religious activity, but also as a forum for instilling Qur'anic and Sunnah values, which are evident in the recitation of Yāsīn, tahlil, and moral lectures delivered in a relevant manner. In addition, this activity also serves as a means to strengthen social solidarity through the traditions of gathering, exchanging information, maintaining emotional relationships, and providing support to residents facing difficulties. The conclusion of this study states that Friday night recitations play a crucial role in preserving the religious identity of rural communities and also in strengthening social bonds. This tradition illustrates how religious teachings can live on and shape a harmonious, sustainable local culture that is rich in values of togetherness.